Mechanisms, actors and impacts of the touristification of a tourism periphery: the Saint-Ouen flea market, Paris. Issue 3 (6th September 2019) - Gravari-Barbas, Maria; Jacquot, Sébastien
Abstract : Purpose: The purpose of this paper is to analyze the mechanisms involved in the progressive integration of marginal and peripheral urban areas, located close to established tourist destinations, into the visited tourism perimeter, and the interplay of the supporting public and private actors. It focusses on the intertwining processes of commercial gentrification, heritagization and aestheticization of former "ordinary" or marginal areas as tools for and indications of their tourism development. It explores how the metropolitan tourism geography is progressively redesigned. Design/methodology/approach: Following a comprehensive literature analysis, the Saint-Ouen flea market was selected as the object of study. The methodology is based on extensive in situ observations, a systematic analysis of the press and a corpus of tourist guides and several in-depth interviews with local public and private stakeholders. Findings: This paper shows that combined public (Parisian urban and tourism stakeholders) and private interests led to the integration in the tourism perimeter of a space that was once on the margins of the tourism and metropolitan area. It highlights the mechanisms of this integration and the link between touristification, gentrification, aestheticization and artification. It was found that private investors and political decision makers regard Saint-Ouen flea market as a major opportunity for tourism and real estate development, which leads to some contradictions regarding heritage protection. Finally, it shows that market traders opposed the evolution of a commercial place into a place of symbolic consumption. At another level, it shows the stakes of tourism diversification in a metropolitan tourism destination that is characterized by overtourism. Research limitations/implications: More studies are needed to identify not only the potential of flea markets to diversify tourist areas and practices, but also any potential resistance. The consequences on metropolitan tourism can be the subject of additional investigations: can this tourism diversification reduce overtourism in the centre, or is it only a diversification that functions as an additional driver of attractiveness? This research opens new perspectives on the modes of diversification (spatial and experiential) of metropolitan tourism as well as on the role that commercial changes play in these evolutions. It also makes it possible to question the modes of engagement of investors and traders in tourism. Originality/value: This is an in-depth analysis of the case of Saint-Ouen flea market. The issues raised herein are applicable to similar peripheral urban areas, flea markets especially, that are rarely studied on the tourism-aestheticization-gentrification nexus. The analysis also shows the diversification of places and imaginaries of metropolitan tourism.